Corrosion behavior of Cu-Al-Be shape memory alloys with different compositions and microstructures - Montecinos Espinoza, Susana de Los Angeles (2013)
The corrosion behavior of Cu–Al–Be shape memory alloys with different microstructures and Be content in a 3.5% NaCl solution was studied by weight loss, cyclic anodic polarization and chronoamperometric measurements. The beryllium has a beneficial effect in β alloys. A pitting potential of −100 mV/SCE was found by anodic polarization tests for all the studied alloys, corresponding to the formation of pits produced by severe dealuminization. Samples with precipitates were more susceptible to pit formation. The corrosion behavior is strongly affected by the alloy microstructural conditions, and the β samples present higher pitting resistance and repassivation ability.